The effect of renal transplantation on quality of sleep in former dialysis patients. (24th October 2016) - Brekke, Fredrik B.; Waldum‐Grevbo, Bård; von der Lippe, Nanna; Os, Ingrid
Summary: Data on sleep quality in renal transplanted (RTX) patients are scarce, and longitudinal studies are lacking. The purpose of this study was to assess the prevalence of sleep complaints in RTX patients and identify variables associated with improvement in sleep quality. In a longitudinal study, 301 dialysis patients were followed for up to 5.5 years, during which time 142 were transplanted. Out of the transplanted patients, a total of 110 were eligible for inclusion. Sleep quality and depression were assessed with the validated questionnaires Pittsburgh Sleep Quality Index (PSQI) and Beck Depression Inventory (BDI), and data were collected during dialysis and after RTX. Based on PSQI scores, 59% were characterized as poor sleepers after RTX compared to 75% when in dialysis ( P = 0.016). A total of 46% experienced a clinical relevant improvement in overall sleep quality, while 21% experienced a clinical relevant deterioration. In multivariable analyses, clinical meaningful change in sleep quality was not associated with either depressive symptoms assessed with BDI or other clinical variables. Sleep quality improved after RTX in nearly half of the patients, but poor sleep quality was prevalent in RTX patients. Therefore, sleep quality should routinely be assessed in RTX patients.